Sleeping Quality Does Not Affect Blood Pressure among Elderly in Tresna Werdha Nursing Home City of Bandung - Vani S Mohani; Titing Nurhayati; Dian M Sari (Universitas Kristen Maranatha, 2018)
AbstractBad sleep quality is often associated with rise in blood pressure. However, there are still differences between measurement done in elderly respondents and other age categories. Thus, the aim of this study is to determine association between quality of sleep with blood pressure among elderly in Tresna Werdha nursing home city of Bandung. This study uses analytical method with cross-section design. Respondents in this study are 51 people with elderly age category. Instruments used are Pittsburgh Sleep Quality Index (PSQI) questionnaire, mercury sphygmomanometer, and stethoscope. PSQI questionnaire is used to measure sleep quality with good sleep quality scores < 5, and bad sleep quality scores ≥ 5. Blood pressure with measurement result < 120 for systolic pressure and < 80 mmHg for diastolic pressure is categorized as normal blood pressure, and hypertension is categorized with measurement result ≥ 140 for systolic pressure and ≥ 90 mmHg for diastolic pressure.This study uses Chi-square analysis test with significance value p<0.05. Result of this study shows p = 0.113 for systolic pressure and p = 0.543 for diastolic pressure, it can be concluded that there is no association between sleep quality and blood pressure among elderly in Tresna Werdha nursing home city of Bandung. Keywords: sleeping quality, elderly, nursing home, blood pressure